Stampel Flash Bagi UMKM Percetakan - Zuliyati Zuliyati; Wiwit Agus Triyanto (Muria Jurnal Layanan Masyarakat, 2021)
UMKM need to increase their productivity through technology upgrades, so that the production process becomes more effective and efficient. This community service partner is UMKM printing "Giga" with the aim of this service activity is to increase partner productivity through the application of technology, namely upgrading one of the products, namely wood stamps into flash stamps. The problems faced by partners are the low management of business management and the unpreparedness of resources in facing technological changes so that businesses are managed conventionally and traditionally. The method of this service activity is to use technology guidance, training on making flash samples and mentoring business management. The output of this activity is sample flash products, increased income, as well as national seminars and publications through scientific articles in the form of dedication proceedings or journals.